PENGEMBANGAN PERANGKAT PEMBELAJARAN PARAGRAPH BASED WRITING MENGGUNAKAN CIRCLE THE SAGE BERBASIS CRITICAL THINKING - Testiana Deni Wijayatiningsih; Akhmad Fathurrahman (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The third semester students have difficulty in composing words into sentences, from sentences into paragraphs to form an interesting, coherent, and cohesive composition. In line with the complex constraints above, it is necessary to do a reflection and an alternative action to the method combined with an interesting learning model. Changes and reflections were made through the development of learning tools for paragraph-based writing courses using circle the sage method based on critical thinking as a stimulus to enable students to be more active and creative in designing coherent and cohesive English writing. The main purpose of this research is to produce instructional device of paragraph based writing course using circle the sage based on criticalthinking. Research method used by researcher is method research and development (research and development). Procedure of development in this research use 4-D model that is define (definition), design (design), develop (development) and disseminate (spread). Data collection techniques used the results of the questionnaire before and after the treatment of learning, a questionnaire fromthe learning device validator. Data analysis using qualitative descriptive that determine the success of development of instructional tool of course paragraph based writing using circle the sage based on critical thinking. The results of this study concluded that there is an increase in learning to write paragraphs with the method of circle the sage based on critical thinking so that the development of learning tools to write paragraphs applicative. Keywords: device development, writing, circle the sage, critical thinking